Online Behavioural Profiling Under the Current Scope of the European Union Law - Partanen, Johanna (My University, 2020)
On the internet, many of the services, such as social media platforms, search engines and news sites, are offered in exchange of data for free of charge to the users. The data provided by the individuals to the service providers is most commonly used for generation of advertising revenue, as well as to provide the individual users a tailored experience. With the purpose of making the service tailored, the service provider must, at a certain level, know who the individual is and what does she desire. Hence, the data collected may be used to create an individual a profile, which is based on her previous online behaviour. Online behavioural profiling is a prevalent practice in the data driven information society. Therefore, the Thesis aims at placing it in the European Union law context to fully comprehend the rights and also potential obligations of the individuals being profiled but also the privileges and responsibilities of the profiler. The Thesis aims at providing an overview of the legislation impacting the conduct of online behavioural profiling by researching online behavioural profiling in light of the European Union legislation. A special emphasis will be given to fundamental and human rights, as well as to the General Data Protection Regulation, that came into force in May 2018. The impacts of the conduct were found manifold in respect to the individuals but also possible broader effects on society discovered, most importantly by hindering the access to information. The obligations to the profilers were mostly derived from the GDPR, but at a certain level other instruments could be stated as imposing obligations, such as the consumer protection law. The Thesis concludes, that the current legislative scope available in the EU is applicable to online behavioural profiling especially in the form of the GDPR. It is averred, too, that certain gaps were found from the legislation especially in connection with areas such as enforcement and individual right to effective remedy, which may obstruct the possibility to control the unwanted behavioural profiling within the Union.
Keywords: Online behavioural profiling, General Data Protection Regulation, Information Society, Eu-ropean Union law, behavioural targeting, online advertising, privacy, data protection